Anti‐inflammatory protective effect of ADAMTS‐13 in murine arthritis models. (4th August 2022) - Fukui, Shoichi; Gutch, Sarah; Fukui, Saeko; Chu, Long; Wagner, Denisa D.
Abstract: Background: Patients with rheumatoid arthritis (RA) have frequent thrombotic events with endothelial dysfunction. Von Willebrand factor (VWF) has been shown to bind neutrophil extracellular traps (NETs) and NETs are part of RA etiology. Objectives: This study aims to elucidate whether this prothrombotic status exacerbates inflammation in arthritis. Here we focus on the involvement of A Disintegrin And Metalloprotease with ThromboSpondin type 1 motif, member 13 (ADAMTS‐13), an enzyme cleaving VWF and its effect on NET deposition and RA development. Methods: We evaluated the influence of the Adamts13 gene and recombinant human ADAMTS‐13 (rhADAMTS‐13) on arthritis in the mouse models of collagen‐induced arthritis (CIA). We also assessed VWF and NETs in synovial tissue. Results: Several Adamts13 −/− mice developed arthritis, while Adamts13 +/+ siblings did not. Synovial tissue from Adamts13 −/− showed accumulation of NETs. Treatment of DBA/1 J mice, an arthritis‐susceptible strain, with well‐tolerated doses of rhADAMT13 reduced arthritis incidence and alleviated the severity of arthritis. Mice treated with rhADAMT13 presented less serum interleukin 6 and less bone erosion determined by micro‐computed tomography. The effects on arthritis severity were observed both when administering rhADAMTS‐13 prophylactically and also when given after arthritis has developed. In both conditions, rhADAMTS‐13 reduced VWF and NET deposition on proliferated synovial tissue evaluated by immunoblotting. Conclusions: Our results demonstrate the inhibitory role of Adamts13 in murine arthritis and the effectiveness of rhADAMTS‐13 treatment. Additionally, this study suggests that deposition of VWF in the synovium and subsequent pathogenic NET retention promotes arthritis. Treatment with rhADAMTS‐13 provides a potential therapeutic approach targeting inflammation and pro‐thrombotic state in arthritis.